Low-Dose Aspirin for Preterm Birth Prevention in Low- and Middle-Income Countries: A Systematic Review and Meta-Analysis - Yeeshana Ganpat; Fiona Campbell (Reproductive Medicine, 2025)
Background/Objective: Preterm births disproportionately affect low- and middle-income countries (LMICs), where evidence-based interventions to improve birth outcomes are lacking. The objective of this study was to systematically review, collate, and synthesize data on low-dose aspirin’s (LDA) effect on the incidence of preterm births in women from LMICs. Materials and Methods: This review included nine randomized controlled trials (RCTs) spanning thirteen LMICs, with 22,545 participants. The intervention group comprised 11,275 participants and the control group comprised 11,270 participants. The relative risk ratios and pooled intervention effects were calculated using Review Manager software, RevMan v5.4.1, with a random effects model. Low-dose aspirin’s effects on five outcomes were analyzed: preterm birth, perinatal mortality, low birth weight, antepartum hemorrhage, and post-partum hemorrhage. The quality of the studies was assessed by the Cochrane risk-of-bias tool and overall quality of evidence, using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Two independent authors participated in screening, data extraction, and quality assessment of the included studies. Results: Low-dose aspirin therapy significantly lowered the risks of preterm births (RR 0.91, 95% CI 0.84–0.98, p = 0.02) and perinatal mortality (RR 0.83, 95% CI 0.73–0.94, p < 0.01) in at-risk pregnant women from LMICs. Its effects on low birthweight and ante- and post-partum hemorrhages were less conclusive. Conclusions: Targeted LDA therapy should be considered to reduce preterm births in at-risk pregnant women from LMICs.